n-i-p Microcrystalline Tunnel Junction in a-Si:H/a-Si:H Tandem Cells - Rubinelli, Francisco Alberto (2001)
The kinetics controlling the electrical transport inside the μc-Si tunnel-recombination junction (TRJ) of a-Si:H/a-Si:H tandem solar cells was studied in detail with computer simulations. Trap assisted recombination tunneling and Poole–Frenkel mechanisms were included in our analysis. Three different μc-Si tunnel junctions were investigated: (a) n-p, (b) n-oxide-p and (c) n-i-p. The highest theoretical efficiencies in a-Si:H/a-Si:H tandem cells were achieved with the n-i-p tunnel junction structure. The impact of the μc-Si effective masses, mobility gap, and mobilities in the tandem solar cell efficiency is also studied in this article. Several a-Si:H/a-Si:H tandem solar cells were made with the μc-Si tunnel configurations of types (b) and (c). In all of these samples one extra oxide layer was needed at the i-a-Si:H/n-μc-Si interface. Both tunnel junctions lead us to comparable experimental tandem solar cell efficiencies. When the n-i-p structure is implemented as TRJ in the a-Si:H/a-Si:H tandem solar cell, efficiencies sensitively depend upon the tunnel junction intrinsic layer thickness. The optimization of this thickness provides a more controlled way of maximizing the tandem solar cell efficiency. Illuminated J–V and QE characteristics were successfully fitted using computer modeling.